Ethnicity, gender, and geographical distribution of dentists in Taiwan in 1939 (Showa 14) - Feng-Chou Cheng; Ling-Hsia Wang; Tzu-Chiang Lin; Julia Yu-Fong Chang; Chun-Pin Chiang (Elsevier, 2024)
Background/purpose: Taiwan's dentistry entered into a new era of modernization and flourished during the Japanese colonial period. However, we know very little about the composition of dentists at that time. This study attempted to analyze the ethnicity, gender, and geographical distribution of dentists in Taiwan in 1939 (Showa 14). Materials and methods: The methods of documentary analysis and secondary data analysis were adopted to find the composition of dentists during the late Japanese colonial period through a name list of contract dentists for the Postal Savings Insurance published in August 1939 (Showa 14) by the Taiwan Government Transportation Department Information Bureau. Results: The total number of contract dentists was 368, accounting for 86.79% of the 424 practicing dentists in Taiwan in 1939 (Showa 14). Of the 368 contract dentists (328 males and 40 females), 225 (61.14%) were Taiwanese and 143 (38.86%) were Japanese. Among the 8 prefectures in Taiwan, Tainan Prefecture had the largest number of dentists (97), followed by Taipei (84) and Taichung (78) prefectures. The number of contract dentists per 100,000 people was 6.24, equivalent to 16,021 people served by each contract dentist in 1939 (Showa 14). The chi-square test for the trend analysis of gender distribution indicated a significantly higher proportion of male than female contract dentists in either Taiwanese or Japanese ethnic group. Conclusion: In the late Japanese colonial period, the number of Taiwanese dentists exceeded that of Japanese dentists. Furthermore, there were more male than female dentists in either the Taiwanese or the Japanese population.